Roles of calcium and Mitochondria-Associated Membranes in the development of obesity and diabetes - Cárdenas Pérez, Robbi Elizabeth; Camacho Morales, Alberto (UANL. Facultad de Medicina, 2016)
Obesity has become a public health problem around the world. According to the Organisation for Economic Co-operation and Development (OECD, 2014 report), more than one in three adults in Mexico are obese. It is known that the hypothalamus, a region of the Central Nervous System (CNS), is actively involved in regulating energy homeostasis during obesity. Anatomically, the hypothalamus is composed of several nuclei coordinating body weight and metabolism, including the arcuate nucleus (ARC), which contains neurons co-expressing orexigenic peptides like Agouti-related protein (AgRP), Neuropeptide Y (NPY) and the anorexigenic peptide Pro-opiomelanocortin (POMC). During obesity, the integration and metabolic response in the ARC is disrupted by three molecular mechanisms: (1) activation of endoplasmic reticulum (ER) stress, (2) mitochondrial dysfunction, and (3) increase of ER and mitochondria contacts, known as Mitochondria-Associated Membranes (MAMs). In this context, it is proposed that MAMs formation induces mitochondrial Ca2+ overload and metabolic dysfunction, leading to insulin resistance and diabetes. Recently, MAMs formation has emerged as one of the molecular mechanisms underlying metabolic alterations during obesity. Thus, in this review we will focus on proposing scientific evidence to support the role of the MAMs and their function on calcium regulation during obesity, as an important pathological mechanism in the development of diabetes mellitus type 2.